Dynamics and sustainability of urban agriculture: examples from Sub-Saharan Africa - Drechsel, Pay; Dongus, S. (Springer, 2010)
Urban agriculture can have many different expressions, varying from backyard gardening to poultry and livestock farming. This article focuses on crop production on larger open spaces in cities of Sub-Saharan Africa (SSA) and investigates the sustainability and dynamics of this type of land use, which is common on undeveloped plots particularly in lowlands, such as in inland valleys, or along urban streams or drains. An adapted version of the Framework for Evaluating Sustainable Land Management (FESLM) developed by the Food and Agriculture Organization of the United Nations (FAO) was used to assess the sustainability of urban agriculture. As an example for dynamics, the spatio-temporal changes of open-space agriculture in Dar es Salaam, Tanzania, are analyzed for the period from 1992 to 2005, and compared with data from other cities. Crop production on urban open spaces appears as a market-driven, highly productive and profitable phenomenon. However, it is often constrained by tenure insecurity and non-agricultural land demands. Also, the common use of polluted water limits the official support of irrigated urban farming. However, despite these constraints, the phenomenon of urban farming appears persistent and resilient to its changing environment, although individual farmers might have to shift to other sites when their plots are needed for construction. Open-space vegetable production in urban areas is a dynamic, viable and largely sustainable livelihood strategy, especially for poor urban dwellers. Spatio-temporal analysis shows that it is not a short-lived or transitional phenomenon - probably as long as it can maintain its comparative market advantage. However, its informal nature and resulting lack of political recognition need to be addressed.